Nuclear Symmetry Energy in Chiral Model of Nuclear Matter - Tuan Anh, Nguyen; Phat, Tran Huu; Tam, Dinh Thanh (Communications in Physics, 2012)
The physical properties of asymmetric nuclear matter are studied in the Extended Nambou-Jona-Lasinio (ENJL) model formulated directly in the nucleon degrees of freedom. It results that the density dependence of the nuclear symmetry energy and its related quantities are basically in good agreement with data of recent analyses